Solitary model of the charge particle transport in collisionless plasma - Simonchik, L.V.; Truhachev, F.M. (Вопросы атомной науки и техники, 2007)
The one-dimensional MHD solitary model of charged particle transport in plasma is developed. It is shown that self-consistent electric field of ion-acoustic solitons can displace charged particles in space, which can be a reason of local electric current generation. The displacement amount is order of a few Debye lengths. It is shown that the current associated with soliton cascade has pulsating nature with DC component. Methods of built theory verification in dusty plasma are proposed.